Peningkatan Kualitas Hidup ODHA Melalui PHBS dan Personal Hygiene - Afrieani Deasy; Meilati Suryani; Atira; Ijun Rijwan; Mona Megasari; Diah Ayu; Mira Eriyanti (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Adopting Clean and Healthy Living Behaviors and maintaining personal hygiene are crucial steps in preserving health and improving the quality of life for people living with HIV/AIDS. However, knowledge regarding PHBS and personal hygiene still needs to be enhanced through health education activities. Objective: This educational activity aimed to increase the knowledge of PLWHA regarding PHBS through the provision of health education. Methods: Pre-test and post-test methods were employed in this activity. Data were analyzed descriptively by comparing the mean scores before and after the education. Results: The evaluation showed a mean pre-test score of 66.8, while the mean post-test score rose to 92.4. This reflects an average increase of 25.6 points, or 38.32%. In the post-test phase, 16 participants (64%) achieved a score of 100, 3 participants (12%) scored 90, 3 participants (12%) scored 80, 2 participants (8%) scored 70, and 1 participant (4%) scored 60. These results indicate that the majority of participants possessed an excellent level of understanding after attending the health education session.